Studio Trad: Facilitating traditional music experiences for music production students. Issue 3 (1st December 2018) - Kearney, Daithí; Commins, Adèle
Many music production programmes in higher education institutions are heavily invested in popular music genres and production values in contrast to the diversity of musics often included in other music programmes and encountered in everyday life. Commenting on his 2017 album, Ed Sheeran highlights the potential for incorporating Irish traditional music into popular music. Over the past number of years, creative practice research projects at Dundalk Institute of Technology have provided opportunities for music production students to engage in the recording and production of Irish traditional music, broadening their experience beyond popular music genres and facilitating time for them to work collaboratively with Irish traditional musicians. Thus, an authentic and action-oriented mode of engagement in higher education is utilized to enhance the learning experience continuously aware of changes and attitudes in the music industry. This article focuses on three Summer Undergraduate Research Projects that provided students with the opportunity to research and record Irish traditional music during the summer months. The project not only provided the students with credible industry-like experience, it also provided the staff involved with an insight into the potential of collaborative project work to address multiple learning aims and objectives. In this article, a critical review of the projects is informed by feedback from the students involved, which can inform future development and structures of existing programmes in music production education.